2012
DOI: 10.1089/ars.2011.4387
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Manifestation of Metabolic Syndrome and Dietary Management

Abstract: With the advent of high-throughput technologies and epigenetic modulation of the metabolic disorders, an altered epigenetic code that is programmed due to improper nutrients can be reverted back by supplementing the diet with various plant-derived compounds. The implication of small molecular drugs is also of utmost significance for challenging the metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 358 publications
0
13
0
Order By: Relevance
“…Given the responsiveness of epigenetic marks to dietary factors, there are numerous studies that try to identify new plant compounds with effects on the epigenetic molecular processes in order to apply them in obesity prevention and treatment (Chaudhary et al, 2012). In a near future, we could talk about "epigenetic foods" that will be a kind of functional foods that contain bioactive compounds with capacity to modulate miRNA expression, DNA methylation or histone modifications.…”
Section: Polyphenols and Other Plant Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the responsiveness of epigenetic marks to dietary factors, there are numerous studies that try to identify new plant compounds with effects on the epigenetic molecular processes in order to apply them in obesity prevention and treatment (Chaudhary et al, 2012). In a near future, we could talk about "epigenetic foods" that will be a kind of functional foods that contain bioactive compounds with capacity to modulate miRNA expression, DNA methylation or histone modifications.…”
Section: Polyphenols and Other Plant Compoundsmentioning
confidence: 99%
“…Some of them could have some benefits in the treatment or prevention of metabolic disorders. Moreover, there is currently great interest in identifying new plant compounds with epigenetic properties that could be applied as therapeutic agents in obesity (Chaudhary et al, 2012). So, numerous plant extracts and compounds are being screened for modulating histone modifying enzymes and DNMTs.…”
Section: Polyphenols and Other Plant Compoundsmentioning
confidence: 99%
“…As DAG is a major regulator of many important biological processes, its abundance in cells might be tightly controlled, which is a key role for DGK [9]. Expression of the gene coding for DGK isoforms such as DGKZ, may be closely regulated accordingly by epigenetic mechanisms, influenced by environmental factors such as diet [42]. Through excessive intake in food, an accumulation of TG can lead to fat storage in ectopic sites, which is associated with dyslipidemia and other obesity-related metabolic complications such as hypertension, glucose intolerance [43], and insulin resistance [44].…”
Section: Discussionmentioning
confidence: 99%
“…Growing body of studies has been conducted to elucidate the molecular effects of dietary constituents on genome-wide multiple-level gene expression and metabolic profiles, exhibiting the arrival of post-genomic era in nutrition and cancer research (3638). The results from these studies are exciting and the new biomarkers have been identified through the dietary intervention studies (39,40). Emerging evidence has demonstrated that the interactions between genes/miRNAs and nutrients or nutraceuticals are significantly implicated in the processes of cancer development and progression (41,42).…”
Section: Nutrients and Nutraceuticals For Pancreatic Cancer Preventionmentioning
confidence: 99%